Microbiota and IPF: hidden and detected relationships: Microbiota in IPF - Fabbrizzi, Alessio; Nannini, Giulia; Lavorini, Federico; Tomassetti, Sara; Amedei, Amedeo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Lung microbiota (LM) is an interesting new way to consider and redesign pathogenesis and possible therapeutic approach to many lung diseases, such as idiopathic pulmonary fibrosis (IPF), which is an interstitial pneumonia with bad prognosis. Chronic inflammation is the basis but probably not the only cause of lung fibrosis and although the risk factors are not completely clear, endogenous factors (e.g. gastroesophageal reflux) and environmental factors like cigarette smoking, industrial dusts, and precisely microbial agents could contribute to the IPF development. It is well demonstrated that many bacteria can cause epithelial cell injuries in the airways through induction of a host immune response or by activating flogosis mediators following a chronic, low-level antigenic stimulus. This persistent host response could influence fibroblast responsiveness suggesting that LM may play a role in repetitive alveolar injury in IPF. We reviewed literature regarding not only bacteria but also the role of virome and mycobiome in IPF. In fact, some viruses such as hepatitis C virus or certain fungi could be etiological agents or co-factors in the IPF progress. We aim to illustrate how the cross-talk between different local microbiotas throughout specific axis and immune modulation governed by microorganisms could be at the basis of lung dysfunctions and IPF development. Finally, since the future direction of medicine will be personalized, we suggest that the analysis of LM could be a goal to research new therapies also in IPF.